Optimum spacecraft attitude control methods for a combined attitude and thermal control system - Al-Khodari, M. Saleh Basha (2011)
Spacecraft missions need efficient and precise attitude control systems. With the aim of reducing the vehicle volume and mass, and for a greater reliability, a system combining the conventional spacecraft attitude control and thermal control systems in a single system is proposed. The combined attitude and thermal control system (CATCS), which can work as an attitude actuator and as a heat pipe, uses the satellite’s excess heat to circulate an electric conductivity fluid in a circular closed duct. The fluid circulation provides an angular momentum that can be used for spacecraft attitude controls. The CATCS system is a maiden solution that combines both the attitude and thermal control systems. The feasibility of CATCS has been demonstrated in a previous study. However, the demonstration is dedicated to a single axis (pitch) attitude control capability using the proportional-integral (PI) controller. The proposed work focuses on improving the performance of the attitude control of LEO small satellites with the CATCS system as an actuator by applying a number of advanced control methods. The thermal control performances and properties are constant as in Ref. (Varatharajoo et al., 2003). In addition, there will be no thermal control degradation. A mathematical model of the satellite is represented based on the assumption that the satellite is a rigid body. First, the classical PI controller has been used for a 3-axis attitude control (roll, pitch and yaw). Then, four advanced control methods have been designed and tested to improve the attitude control performance of a small satellite using the CATCS system. The advanced controllers are: the Active Force Control (AFC) with PI controller (AFC-PI), H2 controller, H∞ controller, and the mixed H2/H∞ controller. The proposed controllers are designed to keep the attitude accuracy below the 0.2. The controllers were applied to a 3-axis satellite attitude control independently. The controllers together with their governing equations are coded in MATLAB and SIMULINKâ for both ideal and non-ideal system numerical simulations. The analysis of the results shows that the H2 controller gives the best attitude control performance compared to the other tested controllers, while the PI controller gives the worst attitude control performance for the reference case. The AFC-PI controller shows much better responses than the solely PI controller. The mixed H2/H∞ control shows good attitude accuracies, while the H∞ control has low attitude accuracies compared to the other advanced controllers. The control gains of the designed controllers are small and reasonable except that of the H∞ controller. However, from the performance figures, it is clear that all the proposed controllers can efficiently provide a full 3-axis control with attitudes accuracies below 0.2. The attitude performances show that the CATCS attitude pointing accuracy can be improved through the proposed advanced control methods.